Factors (Antecedents) Influencing Creation and Fate of Innovations and their Organizations – III - Glor, Eleanor D (Innovation Journal, 2021)
Despite recommendations for more quantitative analyses of public sector innovation factors (Glor, 2014a; de Vries, Bekker and Tummers, 2016), there has been limited examination of them. This paper identifies and explores six factors (ideology, politics, the economy, external support, resources, effects) that influenced the introduction and survival or termination of the first time these public sector innovations and their five organizations (I&O) were introduced in North America. It assesses their key antecedent factors before creation (Time 1) and the same factors again at the time of their fate 15 to 44 years later (Time 2). They were assessed with a new measurement instrument examining the six factors (Glor, 2017a). The tool has 1267 statements (items) and 555 pairs of data, with scoring distributed on a five-point Likert scale. Three expert raters completed the instrument (Glor, 2017b). Based on mean scores, the most important factors in Time 1 (creation of I&O) were found to be the economy, resources, effects and external support and in Time 2 (survival/termination) ideology and politics. This methodology could potentially be used to study the remaining 154 Government of Saskatchewan (GoS) population’s innovations and that of other populations.